Long term complications and prognostic factors in locally advanced nasopharyngeal carcinoma treated with docetaxel, cisplatin, 5-fluorouracil induction chemotherapy followed by concurrent chemoradiotherapy: A retrospective cohort study. Issue 49 (4th December 2020) - Shim, Hyun Jeong; Kim, Hyeon Jong; Hwang, Jun Eul; Bae, Woo Kyun; Chung, Ik Joo; Lee, Dong Hoon; Mi, Yoon Tae; Lee, Joon Kyoo; Lim, Sang Chul; Chung, Jae Wook; Cho, Sang Hee
Abstract : Abstract: This study was conducted to evaluate the long term complications and their risk factors including of survival outcomes in patients with locally advanced nasopharyngeal cancer (NPC) treated with docetaxel, cisplatin and 5-fluorouracil (TPF) induction chemotherapy followed by concurrent chemoradiotherapy (CCRT). Among the patients who were diagnosed as NPC, we consecutively evaluated the late complications in 104 patients who completed 3 cycles of TPF induction chemotherapy followed by CCRT and received regular follow-up by otolaryngologist and oncologist. The prognostic factors for overall survival, relapse free survival and each complication were analyzed based on clinical characteristics. Over a median follow-up of 54 months (range, 7.9–152.9 months), 5-year overall survival rate was 87% for stage II, 89% for stage III, 87% for stage IV patients. The significant prognostic factor for survival is complete response rate after CCRT in multivariate analysis. The most frequent toxicity was ear complication (29.8%) including of hearing loss requiring hearing aid (6.7%) and bone necrosis (3.8%). Decreased renal function over grade 2 was occurred in only 4 patients (3.8%) regardless of the cumulative dose of cisplatin. The long term complications did not affect the survival outcome. Patients who received radiation therapy more than 5400 cGy had better survival outcome than those who did not. However, ear complication was significantly related to radiation dose (≥ 6, 600 cGy) and type of radiation therapy (conventional). Age over 65 years was a significant risk factor for both ear and renal toxicity. In conclusion, close follow-up to monitor long-term complications should be performed in patients treated with TPF induction chemotherapy followed by CCRT treatment, especially in elderly patients. Reestablishing the optimal chemotherapeutic agent during CCRT and adjustment of radiation dose after induction chemotherapy could be helpful to reduce the toxicity associated with the subsequent treatment strategy for locally advance NPC patients.